KHARCHINSKY AND ZARECHNYI VOLCANOES - UNIQUE CENTERS OF LATE PLEISTOCENE MAGNESIAN BASALTS IN KAMCHATKA: STRUCTURAL SETTING, MORPHOLOGY, GEOLOGIC STRUCTURE AND AGE - Volynets O.N.; Melekestsev I.V.; Ponomareva V.V.; Yogodzinski G.M. (My University, 1999)
This paper presents the results of studying the spatial distribution and structural setting of magnesian basalts and andesites in the Northern group of Kamchatkan volcanoes and in the junction zone of the Kuril-Kamchatka and Aleutian island arcs. The morphology and geologic structure of unique Kamchatkan magnesian basalt stratovolcanoes are described: Kharchinsky, Zarechnyi, and the Kharchinsky regional zone of cinder cones. The reported evidence includes the ages and eruptive histories, and productivities of the volcanoes and the volumes and weights of their edifices. The magnesian basalts were erupted 40-50 thousand years ago, for the first time during the Holocene.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен